Probiotics May Improve Serum Folate Availability in Pregnant Women: A Pilot Study - Ballini , Andrea; Signorini , Luca; Inchingolo, Alessio Danilo; Saini, Rajiv; Gnoni , Antonio; Scacco , Salvatore; Cantore, Stefania; Dipalma , Gianna; Inchingolo, Francesco; Santacroce, Luigi (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Probiotics are living microorganisms that confer a health benefit when administered in adequate amounts. There is evidence in the current literature about the importance of probiotic use in pregnancy. The early supplementation of probiotics in the perinatal and postnatal periods seems to have a positive impact on the overall mother’s health and future health of infants. AIM: Our pilot study aimed to test the ability of specific probiotics strains in combination with the kiwi-unique enzyme actinidin to improve the availability of folic acid in 20 pregnant women. METHODS: We investigate 20 pregnant women in early (4–10 weeks) (6 patients), intermedium (11–20 weeks) (6 patients), and late (21–30 weeks) (8 patients) pregnancy. RESULTS: Our findings show that the tested formula promotes increased concentration of serum folate in women’s blood and contributes to the control of blood sugar and body weight, regardless of the gestational period (early, intermediate or late). CONCLUSIONS: Our data support the main results reported in the scientific literature about the importance of probiotics intake in pregnancy.